The nature of scientific discovery : (Smithsonian Institution Press, 1975)
Contents: Conpernicus' birthday in 1473 signaled the beginning of a 500-year Age of Discovery, of which we are still a part. This symposium, organized jointly by the Smithsonian Institution and the National Academy of Sciences, was the major tribute of the United States in the worldwide observance of the Copernican quinquecentennial; it celebrated both the man and the larger theme of the process of discovery itself.